Fibroblast growth factor receptor-1 as a potential therapeutic target in sinonasal cancer - Schroeck, Andreas; Goeke, Friederike; Wagner, Patrick; Bode, Maike; Franzen, Alina; Huss, Sebastian; Agaimy, Abbas; Ihrler, Stephan; Kirsten, Robert; Kristiansen, Glen; Bootz, Friedrich; Lengerke, Claudia; et al. (Head and Neck-Journal For the Sciences and Specialties of the Head and Neck, 2014)
Despite multimodal treatment, sinonasal malignancies have an unfavorable prognosis. The purpose of this study was to elucidate if these tumors harbor amplifications of the fibroblast growth factor receptor 1 (FGFR1) gene, which has recently been identified as a potential therapeutic target in squamous cell lung cancer.One hundred twelve primary tumors (including squamous cell carcinoma [SCC], carcinoma associated with an inverted papilloma, sinonasal undifferentiated carcinoma [SNUC], adenocarcinoma, adenoid cystic carcinoma [ACC], esthesioneuroblastoma, and 9 corresponding lymph node metastases) were assessed by fluorescence in situ hybridization (FISH) for FGFR1 copy number status. Human papillomavirus (HPV) status was assessed by p16 immunohistochemical as a surrogate marker.FGFR1 amplification was found in subsets of sinonasal SCCs (20%), carcinomas associated with an inverted papilloma (33%), and SNUCs (5%). In all cases, metastatic tumor samples shared the same FGFR1 amplification status as the corresponding primary tumor tissue. None of the FGFR1-amplified tumors expressed p16.FGFR1 amplification represents a potential molecular target in a subset of patients with sinonasal cancer. © 2014 Wiley Periodicals, Inc. Head Neck 36: 1253-1257, 2014.
EVALuna2:6681